The effect of microwave hydrothermal treatment on the combustion behavior of sewage sludge - Zechen Jin; Qian Zhang; Qian Zhang; Qian Zhang; Fengxiang Qiu; Weijie Hu; Yuheng Feng; Yuheng Feng; Shuping Zhang (Frontiers in Environmental Science, 2022)
In this study, the thermal behavior of microwave hydrothermal char of sewage sludge (MTC) was compared with dried sludge (DS) and char produced by electric hydrothermal treatment (ETC). The retention ratio of volatile matter in MTC was raised by 51.2% compared with in HTS, while their dewaterability by centrifugation were very close. The kinetic parameters of thermal disposal process of the DS and hydrochars were determined from TG analysis. It was found that the activation energy of combustion was reduced from 44.20 kJ/mol of DS to 47.29 kJ/mol for ETC. For MTC, the activation energy was slightly decreased (43.22 kJ/mol). In addition, the highest weight loss rate (0.49%/min) in combustion was also found for MTC. The evolution of gaseous nitrogen compounds was obtained by FTIR analyzer combined with TG. The results indicated that in devolatilization process, the emission of NH3, the main precursor of NOx in combustion, was postulated to higher temperature for MTC. In conclusion, MTC has a better combustion performance and a close dewaterability compared with to ETC. This study provided a new choice for the pre-treatment method of sewage sludge before combustion.